Endoscopic Mucosal Resection versus Endoscopic Submucosal Dissection for Large Polyps: A Western Colonoscopist’s View - Ian Holmes; Shai Friedland (Clinical Endoscopy, 2016)
To discuss the rationale for the widespread application of endoscopic mucosal resection (EMR) rather than endoscopic submucosal dissection (ESD) in Western centers. In Western centers, EMR is the treatment of choice for most non-pedunculated colorectal adenomas >2 cm in size. EMR is sufficiently effective and safe to be performed without post-procedure hospitalization. Advances in EMR have led to reduced recurrence rates, and recent studies have demonstrated excellent outcomes with endoscopic treatment of recurrent adenomas. While studies from Asia have demonstrated lower recurrence rates with ESD, concern about the higher perforation risk and lengthy procedure time of ESD are two of the barriers preventing widespread adoption of ESD in the West. EMR is likely to continue as the dominant method for the treatment of large colorectal adenomas in Western centers until the limitations of ESD are overcome.